2022
DOI: 10.3390/en15041321
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating the Impact of an Official PEV Charger Deployment Plan on an Urban Grid

Abstract: Plug-in electric vehicles (PEVs) are rapidly increasing all over the world as electromobility is being promoted to reduce the greenhouse gas (GHG) emissions. PEVs locally produce zero emissions and they are more efficient in contrast to internal combustion engine vehicles. On the other hand, the impact of the uncoordinated charging of PEVs is expected to create new challenges for the established distribution grid. This article initially evaluates the impact of uncoordinated charging on the voltage regulation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…It has been concluded that with a high penetration of EVs, and no support from photovoltaic (PV) and ES, the transformers will dramatically age. Furthermore, researchers have dealt with the influence of the charging method on transformers' aging [8][9][10][11][12][13]. The main idea is to find an optimal charging scheme to minimize the impact of EVs' charging demand on distribution transformers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been concluded that with a high penetration of EVs, and no support from photovoltaic (PV) and ES, the transformers will dramatically age. Furthermore, researchers have dealt with the influence of the charging method on transformers' aging [8][9][10][11][12][13]. The main idea is to find an optimal charging scheme to minimize the impact of EVs' charging demand on distribution transformers.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the obtained results, it has been concluded that hierarchical charging strategies are the most desirable in terms of LOL, while the centralized charging strategy (valley filling) has shown the greatest LOL of transformers. In one paper [10], a simple method is used to coordinate the charging process of PEVs to avoid the overloading of transformers by using the fact that idle time represents a significant percentage of EV parking time. In the paper, [11] reducing the impact on transformer aging by implementing the capability of delivering a variable charging rate has been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the charging problem of PEVs has been extensively studied [5][6][7][8][9][10]. In these studies, the electrical-energy-related aspects of the PEV charging problem are managed through different aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Smith et al [5] investigated the effect of variable-rate charging on reducing overload in charging PEVs. In [6], the problem of transformer overload due to PEV charging was investigated by considering different cases of assigning different available transformer capacities to PEV chargers. In [7], the charging demand of PEVs was assessed by considering the category of PEVs, charging strategy, battery capacity, and other factors, and then a corresponding power supply scheme was developed based on the obtained demand.…”
Section: Introductionmentioning
confidence: 99%